The Effect of the Severity of Obstructive Sleep Apnea on Leukocyte Telomere Length, 25 Hydroxy Vitamin D, and Parathyroid Hormonal Concentrations in Asian Indians - Bhatt, Surya Prakash; Guleria, Randeep; Vikram, Naval K. (Frontiers in Neurology, 2021)
Background: Obstructive sleep apnea (OSA) is a common disorder in which breathing repeatedly stops during sleep. Leukocyte telomere length (LTL) and OSA are linked with an increased risk of oxidative stress and inflammation. The possible link between LTL and OSA in Asian Indians has not been evaluated. Thus, the present study aimed to compare the link between LTL and OSA in Asian Indians. Methods: In this study, 300 subjects (obese with OSA, 120; obese without OSA, 110, and non-obese without OSA, 70) were included after overnight polysomnography and a fasting blood sample. Clinical, anthropometry, metabolic markers, insulin, 25-hydroxyvitamin D [25(OH) D], and parathyroid hormones (PTH) levels were investigated. LTL was investigated by a QPCR. Univariate and stepwise multivariate linear regression analyses adjusting for age, gender, BMI and %body fat were conducted while treating LTL as a dependent variable in relation to AHI and other covariates. Results: Obese subjects with OSA had significantly decreased 25(OH) D and increased PTH levels. Mean telomere length (T/S) ratio was significantly shorter in patients with OSA. The adjusted correlation analysis showed that shortening of telomere length correlated with increasing age, apnea-hypopnea index (AHI), oxygen desaturation index, and RDI. Univariate analysis showed that LTL revealed a trend toward a negative correlation with a mean age (B+SE, -0.015+0.0006; p=0.01) and positive correlation with AHI [β +slandered error (SE), 0.042+0.017; p=0.008)]. In the multiple regression analysis, LTL was positively associated with AHI (β +SE, 0.281+0.04; p=0.001) after adjusting for age, sex, BMI, and % body fat. Even when adjusted for confounding factors, 25 (OH) D, and PTH levels, LTL still was related with AHI (β+SE, 0.446+0.02; p=0.05). Conclusion: Our study indicates the presence of an association between LTL and OSA and a significant impact of OSA severity and telomeres shortening in Asian Indians.